Discussion on protein recommendations for supporting muscle and bone health in older adults: a mini review - Groenendijk, Inge; de Groot, Lisette C. P. G. M.; Tetens, Inge; Grootswagers, Pol (Frontiers in Nutrition, 2024)
Muscle and bone tissues are interconnected, and both rely on an adequate protein intake. Recommendations for protein intake for older adults specifically vary across countries. The purpose of this narrative review is to discuss the existing evidence for protein recommendations for supporting muscle and bone health in older adults and to evaluate if a protein intake above the current population reference intake (PRI) for older adults would be scientifically justified. First, this review summarizes the protein recommendations from bodies setting dietary reference values, expert groups, and national health organizations. Next, relevant studies investigating the impact of protein on muscle and bone health in older adults are discussed. In addition, the importance of protein quality for muscle and bone health is addressed. Lastly, a number of research gaps are identified to further explore the added value of a protein intake above the PRI for older adults.